Letramento científico em ciência da linguagem no gênero livro didático de ILA - Florencio, Jane Aparecida (2014)
We consider the present research an addition to the investigations about the discourse of science in textbooks, in the educational setting. Textbooks are genres which popularize the discourse of one field of science to the educational context. In these terms, this research aims at verifying to what extent the concepts, contemporaneously mobilized in the field of Language Science, such as sociocultural learning, language as genre, reading as critical literacy, are popularized in the EAL textbook in such a way that it promotes scientific literacy in AL. Scientific literacy is a complex process that, not just involves reading and writing practices related to the field of science, but refers to the comprehension of the science products, the attitude before the scientific knowledge and the capacity to debate and take a stance before values established by the impact of science. In Language Science, in the EAL textbook, for example, scientific literacy can enable the students to develop argumentation, through dialogue, a social mode of interaction. The corpus of analysis is consisted of three reading sections from the Globetrekker Inglês para o Ensino Médio collection. The analysis is made up of a textual investigation, in which we analyse 44 clauses from the reading activities, and a contextual analysis, in which we investigate the site of Plano Nacional do Livro Didático (PNLD), Guia de Livros Didáticos PNLD 2012, the site of Macmillan Publisher and the Teacher s Guide. As a theoretical methodological reference, we adopt the Critical Genre Analysis approach (MEURER, 2002; MOTTA-ROTH, 2006) that consists of the description, interpretation and explication of context and text of the genre in turn. The results indicate that, in general, the reading activities analysed little promote scientific literacy in Language Science in EAL of the students, in terms of the concepts of sociocultural learning, language as genre, reading as critical literacy. Concerning the sociocultural learning, there is a considerable opening to interaction, by means of dialog, in which students can express and defend their points of view, elaborating argumentation based on the their situated context. However, in relation to the concepts of language as genre and reading as critical literacy, the reading activities privilege other concepts in detriment of these ones. The context of the text is not explored, who writes, to whom and why it is written are aspects which lack mobilization. The activities focus the propositional content and the structural organization of the text. As such, privilege is given to an approach in which language is conceived as a product, not as a process. As for the concept of reading as critical literacy, it receives little emphasis, the reading activities timidly approach meaning making, in terms of amplifying students awareness of how, why and to what interests and views texts can favor. Thus, the role of the teacher as a mediator comes into play, a mediator who offers EAL students a greater number of opportunities which may take them to learning.